MEMAHAMI DUNIA PSIKOLOGI ANAK USIA DINI (AUD) DI TK INGIN JAYA - Jamilah; Seroja Mujapasa, Hannafirsta; Emelia, Rinda; Ikrima Fitri, Nurula; Nabilla, Khairunnisa; Gunawan Putra, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood psychology is a scientific discipline that examines developmental patterns in children aged 0–6 years, encompassing cognitive, language, social-emotional, and motor aspects. This study aims to understand the dynamics of early childhood psychological development at TK Ingin Jaya Jambi through a descriptive qualitative approach. Data were collected via classroom observation, in-depth interviews with teachers and parents, and review of children's developmental records. The findings indicate that children's psychological development varies considerably and is influenced by the quality of family environmental stimulation and teachers' pedagogical competence. The principal finding suggests that a developmentally appropriate practice consistently applied by teachers correlates positively with children's psychological maturity. Key obstacles identified include limited parental understanding of normal developmental milestones and insufficient collaboration between the educational institution and families.